Mutual information-based teamwork evaluation in real-world environments: an exploratory investigation with professional surgeons - Ronca, Vincenzo; Castagneto Gissey, Lidia; Bellini, Maria Irene; Iodice, Alessandra; Aricò, Pietro; Di Flumeri, Gianluca; Giorgi, Andrea; Vozzi, Alessia; Capotorto, Rossella; Bonelli, Stefano; Moens, Laura; Babiloni, Fabio; et al. (Frontiers in Network Physiology, 2025)
PurposeTeamwork involves intricate interactions among individuals or groups with shared goals. It necessitates effective communication, defined roles, decision-making processes, and the allocation of cognitive and emotional resources. Objective teamwork assessment demands a comprehensive set of metrics. Although subjective and behavioral metrics, such as self-evaluation and task completion time, are generally applied, they are prone to bias and a lack of objectivity, highlighting the inherent limitations of capturing the unconscious processes of human behavior.MethodsTo mitigate these limitations, the present study proposed a novel approach to teamwork evaluation based on neurophysiological signals (electroencephalograms, EEGs) compatible with real-world applications, i.e., surgical teams engaged in real-world surgeries. To the best of our knowledge, there is no scientific evidence of an objective teamwork measure performed among more than two members and relying on neurophysiological signals in real-world environments. Therefore, the present work aimed at i) developing and investigating the reliability of an objective EEG-based teamwork index using mutual information (MI) methods and ii) providing additional and objective insights for surgeons’ supervisors in healthcare training.FindingsThe results demonstrated the capability of the EEG-based training index to provide additional and objective information, along with its added value and reliability compared to conventional measures (all R > 0.62, all p < 0.002). Furthermore, the EEG-based teamwork index allowed the determination (all p < 0.001) of surgeons’ experience levels (expert vs novice) in terms of cooperative behavior.ConclusionThe results pave the way for targeted interventions, adaptive training sessions, and optimizations in team dynamics and open up opportunities for applying neurophysiological measurements for teamwork evaluation in all operational fields, where proper and granular teamwork optimization could play a crucial role in terms of safety.